An experimental investigation on the application potential of heterogeneous catalyzed Nahar biodiesel and its diesel blends as diesel engine fuels. Issue 24 (17th December 2018) - Dash, Santosh Kumar; Lingfa, Pradip; Chavan, Supriya B.
ABSTRACT: From the inception of commercialization of biodiesel, feedstock scarcity is a major issue to be pondered upon in developing countries. In this study, an attempt has been made to use an abundantly available underutilized high oil content (67% of Nahar seed kernel) feedstock derived biodiesel in a compression ignition engine. The experimental investigation on diesel engine reveals slightly reduced brake thermal efficiency and excellent exhaust emissions up to 40% blending of Nahar biodiesel with conventional diesel fuel. At full load, compared to diesel fuel, the BTE dropped by 1.64% and 1.83%, whereas the BSFC increased by 5.07% and 6.76% for B30 and B40 blends, respectively. The tested emission parameters such as CO, HC, NOx, and smoke were decreased by 12.66%, 17.99%, 8.31%, and 10.61% for B30 and 4.87%, 12.76%, 7.98%, and 11.78% for B40, respectively, compared to diesel fuel. Abbreviation : BD: Biodiesel; DF: Diesel fuel